Dilema Pengujian Undang-Undang Ratifikasi oleh Mahkamah Konstitusi dalam Konteks Ketetanegaraan RI - Nurhidayatuloh Nurhidayatuloh (Jurnal Konstitusi, 2012)
Constitutional Court is an  state  institution  given  with  the  authority,  by  the constitution, to review act toward constitution, UUD 1945, in the first    and final level of which the decision has binding power. The existence of ratification act becomes a problem to the constitutional enforcement system  in Indonesia. Goverment’s binding to the international conventions/agreements are given on the grounds of ratification by The House of Representatives and the President in the form of act. This is because Indonesia recognizes intenational laws after the adoption of the international coventions/agreements. This “special adoption” regarding international coventions/agreements are formed by national law with the same level as the act. Because of taking the form of an act, it is then becomes a problem whether this ratification act can be categorized in the hierarchy of laws based on Law No. 12 Year 2011 and thus can be judicially reviewed by the Constitutional Court.